POSTOPERATIVE URINARY RETENTION AND DURATION OF CATHETERIZATION AFTER SURGERY FOR PELVIC ORGAN PROLAPSE: A 5-YEAR EXPERIENCE - Aijaz, Saima; Kashif, Urooj; Chughtai, Novera Ghayoor; Malik, Summera; Parveen, Fehmida (Journal of Ayub Medical College Abbottabad, 2025)
Background: Pelvic Organ Prolapse is the descent of pelvic organs and their associated vaginal walls through the vaginal opening. Pelvic Organ prolapse (POP) is a common gynecological condition and its prevalence increases with age. Objective was to compare the postoperative urinary retention in relation to the duration of catheterization after surgery for Pelvic Organ prolapse (POP) among women. Methods: A retrospective study was conducted at the Department of OBGYN. Patients who underwent pelvic organ prolapse (POP) surgery between the years 2013 to 2017 were included in the study. Preoperative evaluation including examination under anesthesia defined type and grade of POP. Data with complete medical record was reviewed and type of surgery, blood loss, operative time, type of anesthesia, duration of catheterization and urinary retention were recorded. Data was divided into group A - retention postoperatively and group B - without urinary retention. Duration of catheterization was compared between the two groups. Results: In our study, post-operative urinary retention was significantly associated with duration of indwelling catheterization (p=0.013). Lowest rate of urinary retention was found in patients with catheterization for at least 48 hours. Upon stratification, operative time was significantly associated with postoperative urinary retention (p=0.012). Conclusion: Postoperative urinary retention is a common complication following pelvic surgery, adding to significant anxiety and patient discomfort. This study revealed optimum duration of catheterization to be 48 hours which can result in improved patient outcome.